Study of the influence of intelligence and gender in the assessment of early math (European Journal of Education and Psychology, 2015)
This study evaluated the influence of gender and intelligence in early maths performance, and detected students at risk of maths learning difficulties. A total of 44 second-year preschool boys and girls (Mean age = 53.75 months) were assessed by 3 different tests: Utrecht Early Numeracy Test (UENT), the Test for the Diagnosis of Basic Skills in Mathematics (TEDI-MATH), and Raven's Progressive Matrices Test. The results found that children with a higher IQ also had higher maths scores. However, no significant differences were found in terms of gender and intelligence, or gender and maths performance.